UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN MIND MAPPING PADA SISWA KELAS XI IPA.3 SMA N 1 KINALI - Hendri Budiman (STKIP Pesisir Selatan, 2017)
Based on the results of student learning IPA.3 Class XI SMAN 1 Kinali in Mathematics was found that results for students in the subjects of Mathematics is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in mathematics sub Using many parts division algorithm to determine the quotient and remainder of the division through Mind Mapping learning model in Class XI SMAN 1 Kinali IPA.3 West Pasaman ,This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 40 students Class XI IPA.3SMA N 1 Kinali. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that Mind Mapping learning model can improve student learning outcomes in mathematics sub Using sukubanyak division algorithm for determining the quotient and remainder pembagiandi SMA N 1 Kinali. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 52.48 (Enough) increased to 83.83 (Good) with an increase of 31.35%.